Cesarean delivery is associated with celiac disease but not inflammatory bowel disease in children - Decker, Evalotte; Engelmann, Guido; Findeisen, Annette; Gerner, Patrick; Laass, Martin; Ney, Dietrich; Posovszky, Carsten; Hoy, Ludwig; Hornef, Mathias W. (Pediatrics, 2010)
OBJECTIVES: The aim of this study was to analyze a possible association between cesarean delivery and enteric inflammatory diseases in children. - METHODS: A retrospective, multicenter, case-control study that included 1950 children was performed in cooperation with 26 university and 16 nonacademic children's hospitals. Information on intestinal disease manifestation, together with mode of delivery and gestational age at birth, postnatal complications, and breastfeeding, was collected by the attending physician from children and their parents who were visiting a gastrointestinal outpatient clinic for Crohn disease (CD; 516 cases), ulcerative colitis (250 cases), celiac disease (157 cases), and other gastrointestinal diseases (165 cases) and control subjects who were visiting ophthalmologic, orthodontic, and dental outpatient clinics (862 cases). - RESULTS: Whereas the rate of cesarean delivery of children with Crohn disease or ulcerative colitis was similar to that of control subjects, a significantly enhanced likelihood of being born by cesarean delivery was found in children with celiac disease compared with control subjects (odds ratio: 1.8 [95% confidence interval: 1.13-2.88]; P = .014). - CONCLUSIONS: The mode of delivery and associated alterations in the development of the enteric homeostasis during the neonatal period might influence the incidence of celiac disease.
Gesehen am 13.10.2023